Case report of a 7-year-old CIPA child with multiple debridement’s and amputations. - Zaidi, Syed Ali Haider; Razak, Sufyan; Syeda Kiran Fatima; Hafiz Abdul Wase; Zaidi, Syed Mohammad Haider; Yousuf, Zeeshan; Naz, Farah; Yousuf, Bilal (International Journal of Endorsing Health Science Research, 2021)
Background: Congenital Insensitivity to Pain (CIPA), otherwise known as Hereditary Sensory and Autonomic Neuropathy Type IV (HSAN IV), is a rarely occurring autosomal recessive disorder encompassed by a group of hereditary and sensory autonomic neuropathies, which was initially described as pure analgesia present congenitally. Its clinical manifestation includes recurrent episodes of infections with unexplained behavior, anhidrosis, mental retardation, and damage to oral structures. Case Presentation: In this case report, we have demonstrated the signs and symptoms of a 7-year-old boy presented to the pediatric out-patient department of Memon Medical Institute Hospital with complaints of multiple fluid-filled blisters since the age of 1 year. He had a history of multiple hospital admissions due to infections, where he was diagnosed with a case of CIPA. Management & Results: Since the diagnosis of this medical condition, the child has undergone multiple debridements of his wound and amputations. The treatment plan was aimed to manage the blisters, prevent self-injuries, and treat orthopedic problems by regular dermal and orthopedic follow-ups. Conclusion: There is no cure for CIPA patients, the families that have CIPA patients must undergo prenatal testing and screening to prevent the birth of another affected child.